Constructing and validating of m6a-related genes prognostic signature for stomach adenocarcinoma and immune infiltration: Potential biomarkers for predicting the overall survival - Yang, Jing; Wu, Zixuan; Wu, Xiaoxi; Chen, Siya; Xia, Xinhua; Zeng, Jianguo (Frontiers in Oncology, 2022)
Background: Stomach adenocarcinoma (STAD) is a kind of cancer that begins in the stomach cells and has a poor overall survival rate. Following resection surgery, chemotherapy has been suggested as a curative method for stomach cancer. However, it is ineffective. The most prevalent alteration that affects cancer growth is N6-methyladenosine methylation (m6A), although the possible function of m6A in STAD prognosis is not recognized. Method: We investigated at 24 m6A in STAD from TCGA and GEO. We established a substantial link between several m6A clusters and the tumor immune microenvironment and identified three m6A alteration patterns with varied clinical outcomes. Furthermore, GSVA and ssGSEA demonstrated that m6A clusters were substantially linked to immune infiltration in the STAD. To further investigate the m6A prognostic signals in STAD, we used Lasso Cox regression to build a m6A-regulator prognostic model. Result: The low-m6Ascore group had a lower rate of immunotherapeutic response than the high-m6Ascore group. ICIs therapy was more likely to help the group with a high m6Ascore. Conclusion: STAD occurrence and progression are linked to m6A-genes. Corresponding prognostic models can help STAD patients forecast their prognosis. m6A-genes and associated immune cell infiltration in the tumor microenvironment (TME) may represent potential therapeutic targets in STAD that should be studied further.